SOME IMPLICATIONS OF THE PROBLEM OF AGE AETD GROWTH IN MARINE FISHES FROM THE INDLWATERS - Qasim, S Z (Indian Journal of Fisheries, 2011)
Growth studies on teleosts from the Indian waters are largely based on length frequency distribui ion, for the simple reason that age determination from other conventional metjiods has been found to be diflScult. In some fishes, where scales, otoliths and other hard parts show clear zonations, it is difficult to conclude that these are formed annually. In all those species, which breed successively over prolonged periods, length frequency distribution will not easily indicate yearly broods. Therefore, it has been suggested that before undertaking the study on growth, some generalized growth characteristics in tropical fishes should be taken into account. Experimental studies on fishes, by keeping them in large cages suspended in the sea, has been suggested as one of the possible approaches for determining their rates of growth. The characteristics of some of the well-known growth parameters have been described and the various methods used for estimating the mortality rates of fishes have been indicated. The method employed by the Indian workers, for estimating the mortality rate, is to change the size structure of the catch into age- structure and then estimate the total instantaneous mortality coeflBcient (z) by comparing the abundance offish at successive ages or from their numbers at successive length groups. From the estimate of z, it is possible to determine both fishing mortality coefficient F and natural mortality coefficient M. The yield from a fishery can be determined by employing the two well-known approaches—the Beverton^Holt approach and Shaefer approach.